THE EFFECT OF EDUCATIONAL VIDEOS ABOUT NEWBORN BABY CARE ON THE KNOWLEDGE LEVEL OF POSTPARTUM MOTHERS - Pande Putu Indah Purnamayanthi; Ni Made Egar Adhiestiani (Midwifery Department, UNS (Universitas Sebelas Maret) Surakarta, 2022)
Background: The existence of the baby involves the mother's mechanical and emotional skills. Factors that can affect the mother's skills in caring for newborns are the mother's readiness to reduce the risk of the health of the newborn. Educational video is one of Health Education Methods that can be done to increase mother's knowledge in caring for newborns. The purpose of this study was to determine the effect of educational videos about newborn care on the level of knowledge of postpartum mothers. Methods: This study was conducted in Badung, Bali in March to April 2022. The method used in this research is Pre-Experimental Design with one group pre-test and post-test design. Sampling method with purposive sampling technique. Result: The results of data analysis using the Wilcoxon Match Pairs Test statistical test obtained p value = 0.000 < (0.05). Then there is a significant effect between the pre and post averages after being given the Newborn Care Education Video and the z value of 5.448 and the z table with a value of = 1.96 which means that z count is greater than z table which can be concluded that there is an Effect of Educational Videos on Newborn Care on the Knowledge Level of Postpartum Mothers. Conclusion: The conclusion of this study is that giving a video of Newborn Care Education can increase Postpartum Mother Knowledge about Newborn Care.